Near Unit Roots and the Predictive Power of Yield Spreads for Changes in Long-Term Interest Rates - Lanne, Markku (The Review of Economics and Statistics, 1999)
The ability of yield spreads to predict changes in long-term interest rates implied by the expectations hypothesis is usually rejected. It is suggested that this rejection is often caused by high persistence in the spread when standard inference is employed. Instead, the asymptotically valid method of Cavanagh et al. (1995) is applied to monthly U.S. data from 1952:1-1991:2. The persistence of the spreads seems to have varied over time, and in subsample analysis, the expectations hypothesis cannot be rejected at the long end of the maturity spectrum.